Regulación emocional en estudiantes del sexto grado de primaria de la institución educativa Nº 60080, Ramón Castilla 2023 - Flores Rebatta, Lizbeht Marilyn (2025)
Diagnosing the levels of emotional regulation in sixth-grade primary school students at Educational Institution No. 60080 in the district of Ramón Castilla during the 2023 school year was the objective of this study. A quantitative-descriptive methodology was employed, involving the participation of 110 students. The results showed that the majority of students exhibited a medium level of emotional regulation (60.4%), positive reinterpretation (59.4%), and a tendency to blame others (44.4%), indicating a moderate management of their emotions and responsibilities. However, a significant percentage faced challenges in key areas: 45.3% displayed a high level of self-blame, which may impact their self-esteem, and 45.3% showed difficulty in gaining perspective, limiting their ability to contextualize situations. These findings suggest the need for targeted interventions to improve emotional regulation, encourage positive reinterpretation, and reduce tendencies toward self-blame and blaming others. Such efforts could contribute to the emotional well-being and maturity of the students.